The Writing Scientific Works Book to Improve The Student Scientific Writing Skill - HL, Nur Ihsan; Nasruddin; Sejati, Andri Estining (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Learning in higher education requires supplementary teaching materials to facilitate lecturers and students in the learning process. Supplemental teaching materials are used as a basis for completing one of the scientific writing courses so that learning objectives are achieved. This study aims to create a scientific writing book that impacts students' scientific writing skills. The research is a research and development type using the 4-D model. The prototype was validated by content, curriculum, learning design and language experts. The validated prototype was tested on small and large groups. The subjects of the small group trial were 10 students each, and the large group (24 students and 21 students). Data were taken using in-depth interviews with FGDs. Data were analyzed descriptively. The instrument used was a questionnaire sheet. After the data was collected, it was analyzed using quantitative descriptive analysis. The results of the study showed that the book was declared very valid. Revisions were made to the material, cover design, conformity to the RPS, and sentence improvements. The trial in the small group obtained results with minor revisions to the technical aspects. The conclusion of this study shows that the scientific writing book developed is feasible to use and effective in improving students' scientific writing skills. This research has implications for developing contextual teaching materials based on student needs to support learning in higher education.